Turchia, Russia e sicurezza energetica europea - Palmas, Francesco (Rivista di studi politici internazionali, 2008)
ABSTRACT - This article analyses some problems of the European security in the field of energy. Its first part emphasizes the role of the Turkish platform as an energy hub: its corridors, whether existent or projected are often alternatives to the Russian ones. Immediately, the key role of Ceyhan arises: this oil terminal in the Gulf of Alexandrette is both crucial and critical, because it is potentially controlled by Cyprus, which lies in a strategically dominant position. The second part of the essay dwells upon the neighbourliness between Ankara and the majority of the Caucasian and the Central-Asiatic countries: as a whole, they are fundamental for the security of the European and Western energy supplies. It would be prudent for Brussels to take this into account when evaluating the added value of Turkey’s proposed entry into the Union. The dynamics of the Russian-European relationship in the matter of energy raises so many problems as to require an entire section of the work: the concluding one. Having overridden the charter of energy, Putin’s Russia has opted for a hard-nosed policy towards its European partners, who are easily outmanoeuvered, being divided. Small concessions to this or that country are allowing Gazprom to penetrate deeply into the European market, not only regarding selling but also the distribution of natural gas. Moreover, the European Energy Community is far from being complete, as can be seen by the slow realization of the energy corridors. When will the regional energy market be fully integrated? The subject under discussion is often replete with technical data, but more narrative and historical sections are not lacking, allowing the reader to better understand the current scenario. What about the sources? The main Italian and international press («Sole24ore», «Corriere della Sera», «Monde», «Financial Times», «International Herald Tribune») have been widely consulted, as have the scientific reviews («Est-Ovest», «Affari Esteri», «RSPI», «Limes», «Géopolitique», «Foreign Affairs», «Politique Étrangère»), which have become ever more sensitive to the problems of energy supplies. As required, the footnotes have been limited to the most relevant articles, as has already done in the case of the available bibliography. Finally, it has been pointed out that Europe should move quickly to reinforce its strategic partnership with Algeria and Norway. Both are Europe’s main gas suppliers after Russia and it would be vitally important to integrate them into the South-Eastern European Energy Community, as well as to prevent Gazprom from building its desired gas cartel. Obviously, the relationship with Turkey is crucial too: we are talking of the fourth artery of the European energy supplies. While Ankara has signed the founding treaty, it has not ratified it yet: its observer status is not enough for a Europe ever more dependent on foreign energy imports. RÉSUMÉ - Cet article touche aux questions de la sûreté énergétique européenne. Dans la première partie, on souligne la fonction comme hub énergétique de la plate-forme turque, tout en parlant des couloirs déjà existants et des ceux in fieri, tous importants car souvent alternatifs à ceux de la Russie. C’est le role de Ceyhan qui émerge tout de suite: ce terminal pétrolier sur le golfe d’Alexandrette est aussi bien crucial que critique, parce que potentiellement contrôlé par Chypre, qui jouit d’une position dominante sur la zone cernée. La deuxième partie du travail s’arrête sur les relations de bon voisinage entre Ankara et la plupart des pays du Caucase et de l’Asie centrale: il s’agit de régions fondamentales pour la sûreté des ravitaillements de l’Ue et de l’Occident. Quiconque les contrôlera disposera d’un pouvoir énorme en termes d’influence politique. Bruxelles ferait bien à ne pas sous-estimer cet atout en évaluant la valeur ajoutée de la Turquie pour l’Union. Très problématiques ce sont aussi les relations bilatérales russo-européennes en matière d’énergie, auxquelles la section conclusive de l’article est vouée. Sans tenir compte de la charte de l’énergie, la Russie de Poutine a désormais choisi de montrer le poing à ses partenaires européens, d’ailleurs aisément maniables en tant que divisés. Des moindres concessions à ce pays-ci et à celui-là vont permettre à Gazprom de pénétrer profondément dans le marché européen, non seulement dans la vente mais aussi dans la distribution du gaz. A son tour, la Communauté européenne de l’énergie est bien loin d’être accomplie, comme l’on témoigne la lenteur des travaux de construction des nouveaux couloirs énergétiques, conditio sine qua non d’un marché régional vraiment intégré. Le sujet abordé a demandé beaucoup de données techniques mais le lecteur ne s’inquiète pas. Il ne vont pas lui manquer des références historiques qui lui permettront une compréhension plus aisée du scénario actuel. A propos des sources, on a atteint à la presse quotidienne, autant italienne qu’internationale («Sole24ore», «Corriere della Sera», «Monde», «Financial Times», «International Herald Tribune»), sans évidemment oublier les revues scientifiques, qui s’ouvrent toujours davantage aux problèmes géopolitiques de l’énergie et de ses sources («Est-Ovest», «Affari esteri», «RSPI», «Limes», «Géopolitique», «Foreign affairs», «Politique étrangère»). On ne s’est borne qu’aux citations les plus prégnantes, comme dans le cas des nombreuses monographies disponibles. En conclusion, on souhaite que l’Europe renforce son partenariat stratégique avec Algérie et Norvège, qui représentent ses principaux fournisseurs de methane après la Russie. Il serait d’une importance vitale de les intégrer dans la Communauté énergétique du Sud-Est européen, pour chercher aussi de bloquer ce cartel du gaz souhaité par Gazprom. Les relations avec la Turquie sont cruciales aussi, étant donné qu’on parle de la quatrième artère des approvisionnements énergétiques de l’UE.